Application of the TOPSIS Method for Electronic Supplier Selection Based on Multi-Criteria - Selviani, Chairunnisa; Nasution, Dewi Aslamiah; Amelia, Nabila; Zulida, Nadya Putri; Salsabila, Nisya Aulia; Syahputra, Muhammad Romi (Lembaga Riset Mutiara Akbar, 2025)
Supplier selection in the electronics industry is highly complex due to the numerous and often conflicting assessment parameters. These parameters include economic aspects, product quality, delivery reliability, and environmental impact. This study uses the TOPSIS method to objectively rank suppliers based on four main criteria with their respective weights: product quality (30%), price (25%), delivery accuracy (25%), and sustainability (20%). Simulation data is used as an example to demonstrate how this method is applied. The assessment results show that PT Green Component (S5) is ranked first with a closeness coefficient of 0.7777, followed by PT Techno Supply (S3) with a score of 0.7577. Sensitivity tests using four weighting change scenarios show stable results, with S5 and S3 remaining in the top two rankings. These findings indicate that balancing product quality and environmental sustainability is a key factor in differentiating competitive advantage in the modern supply chain management era. The TOPSIS approach has proven effective as a structured and transparent framework to assist decision-making in the supplier selection process in the electronics industry.